SOCIAL AND PEDAGOGICAL CONDITIONS OF ACTIVATION OF PROFESSIONAL SELF-DETERMINATION OF SENIOR PUPILS - Protas, O. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Under the conditions of integration of Ukrainian education sector to the European education space foresees specialists’ erudition in the sphere of Pedagogics with the specifics of reorganization of a traditional system and its redirecting to the European standards. Education constantly assists in orientation of a young person to self-fulfillment, projection of professional future and will be a key factor of competitiveness in society during their life. At the present stage the content of education in a general education institution is insufficiently adapted to future needs of pupils due to the absence of an integral system of formation of professional self-determination of senior pupils. That is why, the problem of ensuring system activity raises, which has to solve the tasks of professional self-determination of youth. A social worker of an educational institution acts as a coordinator and organizer of solution of the problem of professional self-determination of schoolchildren, thus, one of his main objectives is to develop the readiness for professional self-determination in the younger generation. In order to solve this problem there appears a need to create effective conditions to enhance the professional self-determination of senior pupils. Purpose of the article – to consider effective social and pedagogical conditions of enhancement of the professional self-determination of senior pupils. Results. Study of readiness for professional self-determination of senior pupils of a general education school showed a low level of such readiness and improperly provided conditions of system activity for its formation. These results showed the need to ensure pedagogical conditions of systemic activity in formation of professional self-determination of pupils. Analysis of research papers on problems of creation of pedagogical conditions of professional self-determination of senior pupils and with consideration of tendencies and content of professional activity of a social teacher, we have singled out effective social and pedagogical conditions of enhancement of the professional self-determination of senior pupils: application of a person-centered approach in interaction with pupils; design of educational control of the process of professional self-determination of senior pupils; keeping to the principle of systemacy and stepping in the process of formation of professional self-determination of pupils; pupils’ mastering the content of the professional orientation course (or upgrading of an existing elective course); application of methods of enhancement of the professional self-determination; organization of practice-oriented study process; expansion of subjects of interaction in the process of professional self-determination of a senior pupil (involvement of psychologists, officials of job centers, vocational centers, centers of social service for family, children and youth, etc.); use of information technology in the education process. Originality. The article reveals the matter of the notion of social and pedagogical conditions of professional self-determination of senior pupils. Taking into consideration the research results, the effective social and pedagogical conditions for enhancement of the professional self-determination of senior pupils were defined. Conclusion. Thus, in the process of the research we have defined effective social and pedagogical conditions that will facilitate the enhancement of the professional self-determination of senior pupils.